To solve the problem, we can first define the ages in terms of Tony's current age \( a \):
- Tony's current age: \( a \)
- Andrea's current age: \( a - 6 \) (since Andrea is 6 years younger than Tony)
In two years, their ages will be:
- Tony's age in two years: \( a + 2 \)
- Andrea's age in two years: \( (a - 6) + 2 = a - 4 \)
According to the problem, in two years, Tony will be three times as old as Andrea. This can be expressed as:
\[ a + 2 = 3(a - 4) \]
Now, let's simplify this equation:
-
Expand the right side: \[ a + 2 = 3a - 12 \]
-
Rearranging the equation gives: \[ a + 2 - 3a + 12 = 0 \] \[ -2a + 14 = 0 \] \[ 2a = 14 \] \[ a = 7 \]
This indicates Tony's current age is \( 7 \) years. Andrea's current age then is: \[ 7 - 6 = 1 \]
Now, let's find the equation among the given options that matches our derived equation:
The original equation can be expressed as: \[ a + 2 = 3(a - 4) \] But, we also notice that: \[ a + 2 = 3(a - 6 + 2) \] is the same as substituting \( (a - 6 + 2) = (a - 4) \).
Hence, the correct equation that can be used to find Andrea's and Tony's current ages from the provided options is:
\[ a + 2 = 3(a - 6 + 2) \]
So the answer is: a + 2 = 3(a - 6 + 2)